From L2 Comprehension Difficulty to Test Anxiety: The Mediating Role of Academic Stress Among Filipino University Students - Bendo, Mhel Cedric D. (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study examined the mediating role of academic stress in the relationship between second language (L2) comprehension difficulty and test anxiety among early-stage Filipino university students in an English-medium instructional context. Using survey data from 80 undergraduate entrepreneurship students, the study employed correlational and mediation analyses with bootstrapped confidence intervals to examine the proposed relationships among variables. The results indicated that greater L2 academic comprehension difficulty was associated with higher levels of academic stress, which in turn was strongly related to increased test anxiety. Mediation analysis revealed that academic stress partially mediated the relationship between comprehension difficulty and test anxiety, as the direct association between comprehension difficulty and test anxiety was substantially reduced when academic stress was included in the model. These findings highlight academic stress as a key psychological mechanism through which linguistic challenges in English-medium instruction translate into test-related anxiety. The study contributes to educational psychology literature by clarifying the L2–stress–anxiety pathway among university students in non-native English contexts. Practically, the results underscore the importance of instructional and support interventions that integrate academic language development with stress-management strategies to reduce test anxiety and promote more effective learning experiences in English-medium higher education settings.
Keywords: Academic stress; Test Anxiety; Second Language (L2) Comprehension Difficulty; Mediation Analysis; Educational Psychology